The Efficiency Consequences of Local Revenue Equalization: Tax Competition and Tax Distortions - Sam Bucovetsky; Michael Smart (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper shows how a popular system of federal revenue equalization grants can limit tax competition among subnational governments, correct fiscal externalities, and increase government spending. Remarkably, an equalization grant can implement efficient policy choices by regional governments, regardless of a wide variety of differences in regional tax capacity, tastes for public spending, and population. Thus, compared to other corrective devices, equalization achieves robust implementation. If aggregate tax bases are elastic, however, equalization leads to excessive taxation. Efficiency can be achieved by a modified formula that equalizes a fraction of local revenue deficiencies equal to the fraction of taxes that are shifted backward to factor suppliers.
Keywords: 330; tax competition; intergovernmental grants